Control evaluation in a LVoD system based on a peer-to-peer multicast scheme - Godoi, Rodrigo (2007)
Providing Quality of Service (QoS) in video on demand systems (VoD) is a challenging problem. In this paper, we analyse the fault tolerance on a P2P multicast delivery scheme, called Patch Collaboration Manager / Multicast Channel Distributed Branching (PCM/MCDB) [13]. This scheme decentralizes the delivery process between clients and scales the VoD server performance. PCM/MCDB synchronizes a group of clients in order to create local network channels to replace on-going multicast channels from the VoD server. Using the P2P paradigm supposes facing the challenge of how often peers connect and disconnect from the system. To address this problem, a centralized mechanism is able to replace the failed client. We evaluate the failure management process of the centralized scheme in terms of the overhead injected into the network and analyse the applicability of a distributed approach to managing the process. Analytical models are developed for centralized and distributed approaches. Their behaviour are compared in order to evaluate whether the distributed scheme can improve the fault management process, in terms of reducing server load and generating better scalability.